Perjanjian Waralaba Dalam Kegiatan Jenis Usaha Ritel - Eko Budi Santosa (SAPIENTIA ET VIRTUS, 2018)
Currently private business sector growing rapidly and having a role as a support to the government in developing economy and open employment for the community, one of the business that developed today is a franchise. The operation of Franchise is agreed in the Franchise Agreement. That Franchise Agreement including Franchise Agreement in the field of retail business is made in the form of a standard Agreement which generally contains an exoneration clause in order to protect the interests of certain party. The standard agreement tends to be considered as one-sided agreement, unbalanced, and unfair to the Franchisee. Agreement facing two unbalanced forces, between parties who have a strong bargaining position with the weaker party bargaining position. Based on the above description of the background, then the formulation of the problem in this thesis research is that to emphasize on the form of the standard clause in the Franchise Agreement for the type of retail business and legal protection for the Franchisee related to financial management’s risk for business operations in Franchise Agreement type of retail business.